Theory of the Wire-Drawing Die Design for the Film Lubrication Regime - Kolmogorov, G.L.; Shevlyakov, V.X. (Engineering Transactions, 1992)
Examples of die design for the wire-drawing in the film lubrication regime are presented. Calculation methods for die parameters taking into account pumping effect of both the force feed nozzle and the die itself have been developed for the case of liquid and viscous-plastic lubricants. Basic formulae necessary for the die parameters calculation providing the separation of the workpiece and die surface by the lubricant film are quoted. The optimal opening value of the force feed nozzle gap assuring the maximal lubricant film thickness in the deformation zone has been determined.